Pengembangan Spektrum Respons Dari Gempa Riwayat Waktu Palu 2018 - Rifaldy, Indra; Sukamdo, Pariatmono (Rekayasa Sipil, 2025)
Indonesia is at the summit of three world plates – the Indonesian plate – Australia, the Eurasian plate, and the Pacific plate, so the earthquake activity that occurs in Indonesia is quite high. On Friday, September 28, 2018, at 18:02 WITA there was an earthquake that shook Palu M 7.4 and a depth of 10 km. This study aimed to build a response spectrum from the 2018 Timeline Earthquake. The maximum spectral values of the vibration were obtained at each vibration period value of the T structure and then imploted into such a vibration spectrum, indicating that the beginning of the production of the response spectrum began with the calculation of the angular velocities and periods of vibration of wi and Ti on the information of the stiffness of ki and mi masses. Using the Central Difference numerical method approaching to the derivative value of the time function or a displacement time derivative, both for velocity parameters and acceleration parameters. The SDOF response consisted of a two-dimensional structure analysis by inserting the parameters of the Palu Response Spectrum 2018, to find out how SDOF Respons.The result from development of the displacement response spectrum were HNE 160,60 cm T2,98 sec, HNN 230,09 cm T4,69 sec, and HNZ 94.43 cm T4,97 sec. Velocity HNE maximum 335,79 cm/d T2,98 seconds, HNN 307.30 cm/de T4,69 sec, and HNZ 143,98 cm/sec T2,11 sec. Acceleration HNE 1480 cm/det2 T0,23 seconds; 1850 cm/det2 T 0,38 sec and HNZ 3773 cm/sec2 0,12 sec.